FUNGSI PERBANKAN DALAM UPAYA MEMBANTU TUGAS PUSAT PELAPORAN DAN ANALISA TRANSAKSI KEUANGAN (PPATK) MENCEGAH TERJADINYA TINDAK PIDANA PENCUCIAN UANG - Kusyadi, I Komang; Rai Setiabudhi, I Ketut; Surya Darmajaya, Ida Bagus (Kertha Wicara : Journal Ilmu Hukum; Vol. 03, No. 03, Juli 2014)
Money laundering is an issue that is difficult to prove, Money laundering is often done by utilizing the services or facilities provided by banks. In Indonesia there is no standard provision of customer data so that the money put in the bank is very likely the result of a crime and money laundering activities. Money laundering, in addition very harmful to society, is also very detrimental to the state, because it can affect or damage the national economy or the financial stability of the country with the escalation of crime. The instrument is an institution for preventing and combating money laundering is the institutional organization center for financial transaction reports and analysis center (Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK)) by the government, as mandated by the enactment of Act No. 8 of 2010 on the prevention and combating money laundering. Then can be formulated banking in Bali on how to help PPATK preventing money laundering and is the barriers faced by banks in helping PPATK in preventing money laundering and how mitigation efforts that have been made. This research use juridical empirical research method to discuss the issue. Then last it can be concluded that position banks in Bali assisting PPATK preventing money laundering optimally performed by the bank by way of coordinating with related institutions such as the PPATK,KPK,BAPEPAM LK and the obstacles encountered by banks in helping PPATK in preventing money laundering is the provision of banking secrecy and banking policies allow a person to save money in a bank in the country by using a pseudonym, weak law enforcement, and the lack of public awareness.
Keywords: Crime, Money Laundering, Banks, Corruption